BEST USE FOR MILK ‐ A REVIEW I‐Effect of breed variations on the physicochemical properties of bovine milk. (4th November 2016) - Chen, Biye; Grandison, Alistair S.; Lewis, Michael J.
Abstract : This article reviews the literature underpinning the concept of 'best use' for milk. In factories where more than one milk product type is manufactured, there is an opportunity to select milk that would be best suited to that product. Also, for those considering producer processing, there is an opportunity to select the most appropriate breed of cow to produce milk, which is optimal for their selected products. It is the aim of this article to provide a better understanding of the genetic factors that influence the properties of raw milk and processed milk products in order to make best use for milk a more viable proposition.